Sensitivity Improvement of A Direct Competitive Elisa for Atrazine by Exploiting Low Cross-Reactivity of An Atrazine-Specific Recombinant Antibody Fab-Fragment - Kusharyoto, Wien; Schmid, Rolf D. (Annales Bogorienses, 2004)
The hapten-binding site of the antibody Fab-fragment K411B specific towards the herbicide atrazine (2-chloro-4-(ethylamino)-6-(isopropyJamino)-1,3,5-triazine) was modified by means of structural modeling and site-directed mutagenesis. A triple mutant (GlnL89Glu/ValH37Ile/GluL3Val) of the Fab-fragment showed an increased affinity towards the hapten H/Cl/C6 (4-amino-6-chloro-l,3,5-triazine-2-(6-aminohexanecarboxylic acid) compared to the affinity of the wild-type Fab-fragment towards the same hapten. However, the mutant exhibited substantially lower affinity towards the hapten H/Cl/C6 than towards atrazine and the hapten iPr/Cl/C6 (4-chloro-6-(isopropylamino)-1,3,5-triazine-2-(6-aminohexanecarboxylic acid), which is usually used in the synthesis of enzyme tracers in ELISA for atrazine. Advantage was taken of the low cross-reactivity and increased affinity of the mutant Fab fragment towards H/Cl/C6 to improve the sensitivity of a direct-competitive ELISA tor atrazine. H/Cl/C6 was covalently conjugated with horseradish peroxidase (HRP), and the conjugate H/CI/C6-HRP was used as enzyme tracer in the ELISA for atrazine. An eight-fold improvement in sensitivity of a direct-competitive ELISA for atrazine could be achieved using the tracer H/Cl/C6-HRP compared to the sensitivity of ELISA using the tracer iPr/Cl/C6-HRP. The detection limit for atrazine was as low as 0.01 i g/l.